PENGARUH MINAT BACA TERHADAP HASIL BELAJAR SISWA - Novia Tri Adinda; Yuyun Elizabeth Patras; Wildan Fauzi Mubarock (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research uses a quantitative method with a causal approach. The respondents were 30 class IV students at SD Negeri Cibening 01. This research was conducted in the odd semester of the 2021/2022 academic year. The research results show that there is an influence between Reading Interest (X) on Student Learning Outcomes on Work Material Around Me (Y) in statistical analysis as proven by the results of significance and regression tests with the regression equation Ῡ = 5.75 + (1.01X). So this means that for every one unit increase in the reading interest variable, student learning outcomes will also increase by 1.01 units. The strength of reading interest (X) on student learning outcomes on work material around me (Y) is proven by a correlation coefficient of (rxy) 0.83 with a determination coefficient of 0.6889. This has shown that the increase and decrease in student learning outcomes is influenced by the level of reading interest of 68.89% while 31.11% comes from other factors, and the results of hypothesis testing H0 are rejected and Ha is accepted because tcount 7.839 > ttable 2.021. Based on the results of data processing and discussion, it can be concluded that there is a fairly large positive influence between interest in reading on student learning outcomes in work material around me. In other words, the greater the level of interest in reading, the higher the student learning outcomes, and vice versa.